(untitled) (Journal of Tikapur Multiple Campus, 2024)
The main objective of this paper is to explore the influence of the construction of skyscrapers on a nation’s economy. It explores how skyscrapers influence the economic status of the nation worldwide. Drawing from an extensive literature review and the researcher’s insights, the article underscores the growth of Asian and Western skyscrapers and their influence on the nation’s economic status. It places equal emphasis on the historical aspects, with a vital role regarding the nation’s economy and the economic crisis due to the construction of skyscrapers. Thematically, the researcher analyzed the literature regarding the construction of skyscrapers and its impacts and challenges. Firstly, the role of skyscrapers on the economic growth of a nation is described in detail, and the data related to Asian and Western high-rise buildings is reviewed. It shows that skyscrapers play a vital role in developing the economic condition of some nations. Secondly, the influence of the construction of tall buildings is also reviewed deeply, as well as the challenges and opportunities faced by the people and nation, like the economic crisis due to significant investments in skyscrapers. Overall, the high skyscrapers are the glory and identity of the nation. It enhances the nation’s economic progress rather than being a burden.